Design and Development of Web-Based Extracurricular Management Information Systems at SMP Plus Nuurul Muttaqiin - Budiman, Tedi; Nugraha, Yopi; Ubaeduloh, Ubu (RISTEC : Research in Information Systems and Technology, 2024)
Nuurul Muttaqiin Plus Middle School does not yet use a web-based information system, still manually using a regular recording book. This information system is an information system used to help manage the implementation of extracurricular activities. So that the management of activities can be controlled and recorded well. In developing the extracurricular management information system at SMP Plus Nuurul Muttaqiin, the waterfall method was used for data collection. This information system was created using the PHP programming language and MySQL database. This web-based extracurricular management information system testing method uses black box and usability testing. The result of this research is a website-based information system that can make it easier for teachers and extracurricular members to collect data on the implementation of extracurricular activities so that they can be well controlled. The results of testing the software developed obtained a functionality score of 1 (Good), testing the usability aspect obtained results with a percentage of 94.66% (Very Feasible).Keywords : information system, extracurricular management, waterfall, website